Respostas
respondido por:
0
4+x(x-4)=x
4 + x² - 4x = x
x² - 4x - x + 4 = 0
x² - 5x + 4 = 0
a = 1 b = - 5 c = + 4
Δ = b² - 4.a.c
Δ = (- 5)² - 4.(1).(+4)
Δ = + 25 - 16
Δ = 9
x = - b ± √Δ
2.1
x = - (- 5) ± √9
2.1
x = + 5 ± 3
2
x'= 5 + 3 = 8 = 4
2 2
x" = 5 - 3 = 2 = 1
2 2
S[1 ; 4]
4 + x² - 4x = x
x² - 4x - x + 4 = 0
x² - 5x + 4 = 0
a = 1 b = - 5 c = + 4
Δ = b² - 4.a.c
Δ = (- 5)² - 4.(1).(+4)
Δ = + 25 - 16
Δ = 9
x = - b ± √Δ
2.1
x = - (- 5) ± √9
2.1
x = + 5 ± 3
2
x'= 5 + 3 = 8 = 4
2 2
x" = 5 - 3 = 2 = 1
2 2
S[1 ; 4]
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás